Contribution of Grip Strength and Back Muscle Flexibility to Slice Service Accuracy in Tennis Court UKM Muhammadiyah University of Surakarta - Muhammad Fahrizal Hidayat; Gatot Jariono (CV. Inara, 2021)
The study aims to analyze the contribution of grip strength and back muscle flexibility to slice service accuracy in tennis court UKM Muhammadiyah University of Surakarta. The population and samples used were Students with Interests, Talents, tennis court the Sports Education Muhammadiyah University of Surakarta, totaling 14 students with sampling technique is purposive sampling. While research sampling techniques using systematic random sampling with a type of systematic random sampling. This is seen from the results of the analysis obtained the value Rsquare 0.369 or (36.9%) with a probability level of 0.369 >a 0.05, which is explained through the regression equation value Y = 10.124 + 0.409 X1 + 0.435 X2. These results show that there is a contribution of grip strength and muscle flexion to the accuracy of the slice service in UMS court tennis UKM. Third hypothesis result: there is a significant contribution together between grip strength and muscle flexion together to the precision of the slice service in UKM tennis court UMS. These results show that the strength of the grip and flexibility of the muscles together in UMS court tennis UKM increase simultaneously, it will also be followed by an increase in the accuracy of the slice service in the sport of court tennis. Thus, the strength of the grip and flexibility of the muscles is a combination of two components of physical ability that need attention in court tennis in the future